High Order Thinking Skills (HOTS) Of Ibtidaiyah Madrasah Teacher Education Program (PGMI) Study Program Students During The Covid-19 Pandemic - Siti Sarah (Jurnal Serambi Ilmu, 2024)
High Order Thinking Skills (HOTS) are competencies that are required for students to live in the 21st century. The Covid-19 pandemic makes learning to be done with the help of the media to avoid the spread of the Corona virus. Despite the Covid-19 pandemic. The achievements of HOTS are still being pursued in achieving quality education in the 21st century. This study aims to determine the HOTS achievement of the ibtidaiyah madrasah teacher education program (PGMI) students during the Covid-19 pandemic. The research design is in the form of a survey. The research subjects were all students of PGMI, State Islamic University Professor K.H. Saifuddin Zuhri in the fourth semester of the 2020/2021 academic year. A total of 32 test questions that have met valid and reliable qualifications were used to measure student HOTS. Data analysis used descriptive quantitative. The results showed that the HOTS achievement of PGMI college students was still low. This research is important to do as a material for determining the best learning strategy in order to achieve better HOTS for PGMI college students